PENGARUH SUMBER DAN PENGGUNAAN MODAL KERJA TERHADAP PROFITABILITAS DAN RISIKO (Suatu Kasus Pada Kopkar âDwi Karyaâ di Lampung Tengah) - -, Yateno (Jurnal Manajemen dan Keuangan, 2011)
Sources of working capital held by MAESA Dwi Karya is very supportive and quite adequate for operating capital into two business units, based on research within the last 5 years, the source of working capital derived from three sources, but the most dominating to meet working capital most of the first sequence is a sequence of short-term debt while the second is the capital itself and the rest is obtained from long-term debt. The results show that the business unit Waserda absorb very large compared to working capital savings and loan business units, but unit members Waserda generate net participation or co-operative surplus is smaller than the savings and loans obtained by the unit, the difference in cost is the difference in percentage (%) means that both business units are the most economical and efficient use of working capital and net to obtain the participation of members of the (PNA) or cooperative is a business unit of surplus savings and loan. Effect of profitabiltias, profitability or net participation relative setabil members and tend to increase, but on average, two units above the net cost of participation is still above the average of the set targets, which meant the target was the target of profitability or net participation of members. Influence of risk, business risk MAESA Dwi Karya Dalan period of 5 years is very small not even exist, because the two business units (Waserda and savings and loans) shows that the value of the average standard deviation for the business unit and the unit Waserda registration 0.419425 savings and loans amounting to 0.72628, standard deviation apabilla addressing negative value then the business risks faced by MAESA Dwi Karya is quite large.Keyword: source, use working capital, profitability and risk